Plankton Diversity in the Coastal Waters at Klumpang Beach, East Nusa Tenggara, Indonesia - Muhammad Abdus Salam Jawwad; Hafidya Norista Pramesti; Restu Hikmah Ayu Murti (Nusantara Science and Technology Proceedings)
Planktons represent aquatic organisms that float in the water with relatively passive movement. In ecological function, the distribution of biomass and the species composition of plankton have essential effects on the primary and initial producers of chains in food webs. To preserve nature and biota in the estuary area, monitoring plankton as a bioindicator is necessary. This research aims to study the abundance and diversity of planktons as a bioindicator in the Klumpang beach estuarine region of Labuan Bajo, NTT province, Indonesia. In addition, it also examines the quality of the waters and the level of water pollution based on the diversity index and dominance index. Klumpang beach shoreline has a medium diversity index, adequate productivity level, balanced ecosystem, and medium ecological pressure. The three sampling points have a Shannon-Wiener diversity index of 2.122, 1.509, and 2.296 by sequence. Calothrix sp. becomes the most abundant phytoplankton can be found in all examined sampling points, which indicates a good productivity level and warm temperature of the water. However, the species' unbalanced distribution may indicate an unstable ecosystem in the shoreline, as the impact of surrounding activities.